Pengaruh Kompetensi dan Motivasi Terhadap Kinerja Pegawai dengan Disiplin Kerja sebagai Variabel Mediasi - Shokhibul Lutfi; Adya Hermawati; Dharmayanti Pri Handini (Universitas 17 Agustus 1945 Semarang, 2024)
The purpose of this study was to evaluate the impact of Competence and Work Motivation on Employee Performance and also the role of Work Discipline as a moderator variable. The population used in this study were all civil servants at the Senori District Office, Tuban Regency, and the sample taken using saturated or census sampling techniques, with a total of 37 respondents. Data analysis used Smart Partial Least Square (PLS) software.The results of this study indicate that good competence will improve employee performance, also with good motivation will improve employee performance. This study also found that work discipline can improve employee performance. Furthermore, it was also found that work discipline has a strong moderating role on competence towards employee performance, and has a moderating role on motivation towards employee performance at the Senori District Office, Tuban Regency.